The Customer is NOT Always Right? Marketing Orientationsin a Dynamic Business World : Proceedings of the 2011 World Marketing Congress - Campbell, Colin L. (Springer International Publishing : Imprint : Springer, 2017)
This volume includes the full proceedings from the 2011 World Marketing Congress held in Reims, France with the theme The Customer is NOT Always Right? Marketing Orientations in a Dynamic Business World. The focus of the conference and the enclosed papers is on marketing thought and practices throughout the world. This volume resents papers on various topics including marketing management, marketing strategy, and consumer behavior. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy's flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.
Keywords: Business.; Internet marketing.; Customer relations -- Management.; Leadership.; elektronické knihy; electronic books